PERAN KOMITE SEKOLAH DALAM IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH MENUJU INDONESIA EMAS - Abdul Jabar Idharudin; Abdurrahman; Nurwahida; Samsuddin (As-Sulthan Journal of Education, 2025)
The community can become a partner for schools in preventing student delinquency that occurs outside of school. Schools often face problems with students' parents due to disharmonious relationships. Based on this background, it is concluded that education experiences obstacles in its implementation. Therefore, it is important to examine the role of the school committee in school-based management to realize educational progress as a shared concern. This research formulation is integrated with a case study at SDIT Al-Hidayah Bogor, using qualitative research with a case study approach through data collection in the form of observation, interviews, and documentation. The results of the study show that the role of the SDIT Al-Hidayah committee in implementing school-based management has been well applied in accordance with government regulations and the AD/ART formulation towards "Indonesia Emas" (Golden Indonesia). The SDIT Al-Hidayah committee plays an important role in improving the quality of education at SDIT Al-Hidayah through the following aspects: a) Providing input in determining and implementing education policies at SDIT Al-Hidayah; b) Supporting the implementation of education at SDIT Al-Hidayah, both in terms of financial, intellectual, and labor resources; c) Acting as a controller to ensure transparency and accountability in the implementation and outcomes of education at Al-Hidayah; d) Mediating between the government and the community at SDIT Al-Hidayah.